Kebijakan Pengetesan Kemiskinan sebagai Strategi Penurunan Stunting : Pendekatan Ekonomi Politik - Yessy Ramawati Shaputri; Muhammad Ikhzwan; Naldi Sapril (Kajian Ekonomi dan Akuntansi Terapan, 2025)
Stunting is a type of long-term childhood malnutrition that is closely linked to socioeconomic conditions and poverty. The purpose of this study is to look at strategies to reduce stunting in Indonesia using a political economy approach. To achieve this goal, a literature review method was used. The results show that there are many factors that influence stunting, including health issues and inequalities in power distribution, resource allocation and social structure. Through specific interventions (such as the First 1000 Days of Life program) and sensitive interventions (such as the provision of clean water, sanitation, education, and social protection), poverty alleviation policies are essential to reduce the prevalence of stunting. However, decentralization, poor coordination between sectors, and lack of public awareness often hinder policy implementation. To tackle stunting sustainably, the political economy approach emphasizes the need for clear political alignment, strengthened institutional capacity, and cross-sectoral integration. Stunting is a type of long-term childhood malnutrition that is closely linked to socioeconomic conditions and poverty. The purpose of this study is to look at strategies to reduce stunting in Indonesia using a political economy approach.